2021
DOI: 10.1016/j.arth.2021.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Hueter Anterior Approach for Metal-on-Metal Hip Resurfacing Arthroplasty: 555 Cases at a Minimum Five-Year Follow-Up

Abstract: Background: Purpose of this study was to determine implant survivorship and resultant outcomes, including modes of failure, for metal-on-metal hip resurfacing through the Hueter anterior approach (HAA). Methods: Retrospective review of cases from 2006 to 2015, resulted in 555 metal-on-metal hip resurfacing via HAA, mean age 49.4 ± 6.9 years and mean BMI 28.1 ± 5.3. Kaplan-Meier curves were used to assess implant survivorship. Evaluation of technique was based on radiographic assessment of component position at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The posterior approach is the most commonly used for total hips and hip resurfacing, however in the last decade, the anterior approach has provided as high a level of quality of care for patients requiring joint replacement surgery. 20,21 We have previously reported our overall experience with the HAA for hip resurfacing: excellent survivorship of 95.0% at 5 years and 92.5% at 10 years, 6 with females demonstrating high failure rates due to aseptic loosening and pseudotumour/ALTR. 22,23 One of the key challenges in revision hip surgery is having adequate bone stock for implant fixation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The posterior approach is the most commonly used for total hips and hip resurfacing, however in the last decade, the anterior approach has provided as high a level of quality of care for patients requiring joint replacement surgery. 20,21 We have previously reported our overall experience with the HAA for hip resurfacing: excellent survivorship of 95.0% at 5 years and 92.5% at 10 years, 6 with females demonstrating high failure rates due to aseptic loosening and pseudotumour/ALTR. 22,23 One of the key challenges in revision hip surgery is having adequate bone stock for implant fixation.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 The Hueteranterior approach (HAA) with its limited soft tissue and internervous dissection has been shown to be a reasonable alternative to more extensile approaches when performed for HRA. 6 In addition, anterior approaches have been advocated by some authors for advantages in revision total patients. 10 Although ease of revision is one of the proposed advantages of hip resurfacing, clinical studies of revised HRA have shown variable outcomes tied with the indication for revision.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, regarding the safety of the two procedures, THA was associated with higher mortality rates, compared to HRA [ 11 , 12 ]. Overall, the main advantages of HRA were with regards to reproduction of natural joint biomechanics, conservation of femoral bone stock, meeting the functional demands and the option for future THA [ 6 , 13 ]. However, the higher incidences of long-term complications after HRA have limited its clinical applications [ 2 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%